Case report: Monoclonal antibodies as an alternative treatment for new daily persistent headache - Ernesto M Bancalari; Natalia Hernández; Analia Soria; Osvaldo Bruera (SAGE Publishing, 2023)
Background: New Daily Persistent Headache (NDPH) is a disabling daily headache that causes huge frustration for patients and headache specialists. Elevated TNF-alpha levels, that elevate CGRP levels, on the CSF of NDPH patients has been described as a possible cause of this disease. TNF-alpha inhibitors like doxycycline, venlafaxine, montelukast and lithium have been used in the past to treat NDPH patients, with relatively good success as described from case reports. Conclusion: We report three NDPH patients that improved with the administration of Anti CGRP monoclonal antibodies (mAbs), after trying multiple treatments. We propose this class of drugs, as a therapeutic option for NDPH.